Prognostic value of transforming growth factor beta receptor 1 polymorphisms in patients with oral cancer. (13th November 2019) - Chen, Lin; Chen, Fa; Wang, Xiaoxia; Chen, Qing; Lin, Jing; Bao, Xiaodan; Wang, Rui; Wang, Jing; Yan, Lingjun; Lin, Lisong; Qiu, Yu; Pan, Lizhen; et al.
Abstract: Objective: To investigate possible associations between disease‐specific survival (DSS) of oral cancer and single nucleotide polymorphisms (SNPs) in transforming growth factor beta receptor 1 ( TGFBR1 ). Methods: Using iPLEX Sequenom MassARRAY platform, three SNPs in TGFBR1 gene were genotyped in 356 newly diagnosed patients with histologically confirmed primary oral cancer. Demographic and clinical information of all cases were obtained from face‐to‐face interviews and electronic medical records, and telephone interviews were carried out every 6 months to timely gain follow‐up data. Univariate and multivariate Cox proportional hazards model were used to assess the association between the polymorphisms of tagging loci and DSS of oral cancer. Results: TGFBR1 rs33438 polymorphism was protective against death of oral cancer in codominant (AG vs AA: HR = 0.55, 95% CI = 0.35‐0.88) and dominant (GG + AG vs AA: HR = 0.57, 95% CI = 0.38‐0.87) models. Moreover, better DSS was particularly significant in radiotherapy patients who carrying GG + AG genotype. There also existed a positive multiplicative interaction on DSS between the polymorphism of TGFBR1 rs334348 and radiotherapy ( P = .001). Not any associations between TGFBR1 rs334354 or rs3739798 polymorphism and DSS were observed. Conclusions: This preliminary prospective study suggests that polymorphism of TGFBR1 rs334348 may act as a potentially independent factor and novel genetic biomarker to predict oral cancer DSS especially for patients with radiotherapy. A much more extensive investigation will need to confirm our findings.